Global classification and coding of hypersensitivity diseases - An EAACI - WAO survey, strategic paper and review. - Demoly, P.; Tanno, L K; Akdis, C. A.; Lau, S.; Calderon, M. A.; Santos, A F; Sanchez-Borges, M; Rosenwasser, L. J.; Pawankar, R.; Papadopoulos, N. G. (Allergy, 2014)
Hypersensitivity diseases are not adequately coded in the International Coding of Diseases (ICD)-10 resulting in misclassification, leading to low visibility of these conditions and general accuracy of official statistics. To call attention to the inadequacy of the ICD-10 in relation to allergic and hypersensitivity diseases and to contribute to improvements to be made in the forthcoming revision of ICD, a web-based global survey of healthcare professionals' attitudes toward allergic disorders classification was proposed to the members of European Academy of Allergy and Clinical Immunology (EAACI) (individuals) and World Allergy Organization (WAO) (representative responding on behalf of the national society), launched via internet and circulated for 6 week. As a result, we had 612 members of 144 countries from all six World Health Organization (WHO) global regions who answered the survey. ICD-10 is the most used classification worldwide, but it was not considered appropriate in clinical practice by the majority of participants. The majority indicated the EAACI-WAO classification as being easier and more accurate in the daily practice. They saw the need for a diagnostic system useful for nonallergists and endorsed the possibility of a global, cross-culturally applicable classification system of allergic disorders. This first and most broadly international survey ever conducted of health professionals' attitudes toward allergic disorders classification supports the need to update the current classifications of allergic diseases and can be useful to the WHO in improving the clinical utility of the classification and its global acceptability for the revised ICD-11.